1991
DOI: 10.1111/j.1399-0004.1991.tb03039.x
|View full text |Cite
|
Sign up to set email alerts
|

Piebaldism: an autonomous autosomal dominant entity

Abstract: Piebaldism is a disorder in which the major clinical features are patchy hypopigmentation of the skin and a white forelock. The manifestations of piebaldism overlap with those of other genodermatoses, in particular the Waardenburg syndrome, and it is uncertain whether piebaldism is a distinct entity. We have documented a family in which seven affected members in three generations have gross piebaldism without any additional stigmata. The intrafamilial phenotypic consistency is suggestive that this autosomal do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…c-Kit is essential for melanogenesis, as demonstrated by the pigmentation defects of mice and humans with loss-of-function mutations in c-Kit (Silvers, 1979;Winship et al, 1991). However, past works, showing that c-Kit expression is usually lost in melanomas (Lassam and Bickford, 1992) and that its restoration in metastatic melanoma cells even results in tumor apoptosis (Huang et al, 1996), pointed to the idea that c-Kit did not play a role in promoting melanomas.…”
Section: Tumors Of C-kit Expressing Cellsmentioning
confidence: 99%
“…c-Kit is essential for melanogenesis, as demonstrated by the pigmentation defects of mice and humans with loss-of-function mutations in c-Kit (Silvers, 1979;Winship et al, 1991). However, past works, showing that c-Kit expression is usually lost in melanomas (Lassam and Bickford, 1992) and that its restoration in metastatic melanoma cells even results in tumor apoptosis (Huang et al, 1996), pointed to the idea that c-Kit did not play a role in promoting melanomas.…”
Section: Tumors Of C-kit Expressing Cellsmentioning
confidence: 99%
“…In South Africa, Selmanowitz et al (1977) published a pedigree with at least 10 piebalds in four generations. Winship et al (1991) reported seven piebalds in three generations living in a rural community east of Cape Town. The founder came from the Xhosa tribe.…”
Section: To the Editormentioning
confidence: 99%
“…Oiso et al (2013), stated that piebaldism illustrated by congenital white skin, commonly known as leukoderma and white hair (poliosis) on the frontal scalp, forehead, ventral trunk, and extremities. Winship et al (1991) have studied a South African family in which nine members extend four generations had piebaldism, and it is shown in the pedigree was indicates autosomal dominant inheritance. To Balo lives in a distant place in the Bulu Pao Mountains, which stretch across the Barru and Pangkep town, Pujananting District, South Sulawesi.…”
Section: Introductionmentioning
confidence: 99%